When and how to say goodbye: An analysis of Standard Operating Procedures that guide end-of-life decision-making for stranded cetaceans in Australasia. (April 2022) - Boys, Rebecca M.; Beausoleil, Ngaio J.; Betty, Emma L.; Stockin, Karen A.
Abstract: Standard Operating Procedures (SOPs) are tools used to ensure management best practice during emergency incidents including wildlife interventions, such as cetacean strandings. The compromised state of stranded cetaceans means humane end-of-life decisions may be considered, and SOPs frequently guide this process. This study evaluated SOPs for end-of-life decision-making and technically enacting euthanasia of stranded cetaceans across Australasia. The aim was to highlight similarities and differences in management and explore directions to improve stranded cetacean welfare. SOPs were requested from the eight government authorities across Australia and New Zealand. All SOPs were evaluated for decision-making criteria, yielding 29 parameters for the implementation of end-of-life decisions. Euthanasia and palliative care were options for end-of-life, with palliative care recommended when euthanasia was not feasible or presented human safety risks. Three euthanasia methods were recommended. Ballistics was recommended in seven SOPs, chemicals in five and explosives in three SOPs. Variability existed in the exact procedures and equipment recommended in all three methods. Additionally, only five SOPs provided criteria for verifying death, while only two recommended time-to-death be recorded, hindering evaluation of the welfare impacts of end-of-life decisions and euthanasia procedures. Our findings highlight the need for detailed guidance and consistency in end-of-life decisions and euthanasia techniques to ensure reliable welfare outcomes. Systematic, standardised data collection at euthanasia events across regions is required to facilitate assessment of welfare impacts and develop evidence-based recommendations. International collaboration is key to developing objective criteria necessary to ensure consistent guidance for end-of-life decisions. Highlights: Standard Operating Procedures (SOPs) for cetacean end-of-life decisions were studied. 8 SOPs across Australasia were evaluated to identify recommended practices. 3 recommended methods of euthanasia, varying in procedure and equipment required. 5 SOPs contain criteria to verify death, 2 SOPs require assessment of time-to-death. Detailed guidance for end-of-life processes is vital to safeguard animal welfare.